Atomically dispersed Ir/α-MoC catalyst with high metal loading and thermal stability for water-promoted hydrogenation reaction. Issue 1 (10th February 2021) - Li, Siwei; Cao, Ruochen; Xu, Mingquan; Deng, Yuchen; Lin, Lili; Yao, Siyu; Liang, Xuan; Peng, Mi; Gao, Zirui; Ge, Yuzhen; Liu, Jin-Xun; Li, Wei-Xue; et al.
ABSTRACT: Synthesis of atomically dispersed catalysts with high metal loading and thermal stability is challenging but particularly valuable for industrial application in heterogeneous catalysis. Here, we report a facile synthesis of a thermally stable atomically dispersed Ir/α-MoC catalyst with metal loading as high as 4 wt%, an unusually high value for carbide supported metal catalysts. The strong interaction between Ir and the α-MoC substrate enables high dispersion of Ir on the α-MoC surface, and modulates the electronic structure of the supported Ir species. Using quinoline hydrogenation as a model reaction, we demonstrate that this atomically dispersed Ir/α-MoC catalyst exhibits remarkable reactivity, selectivity and stability, for which the presence of high-density isolated Ir atoms is the key to achieving high metal-normalized activity and mass-specific activity. We also show that the water-promoted quinoline hydrogenation mechanism is preferred over the Ir/α-MoC, and contributes to high selectivity towards 1, 2, 3, 4-tetrahydroquinoline. The present work demonstrates a new strategy in constructing a high-loading atomically dispersed catalyst for the hydrogenation reaction. Abstract : Atomically dispersed Ir/α-MoC catalyst with high metal loading exhibits remarkable activity, selectivity and stability for quinoline hydrogenation reaction through water-promoted hydrogenation mechanism.